SIMULASI PERANCANGAN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA ON-GRID PADA BARBERSHOP GAUL DENGAN MENGGUNAKAN HELIOSCOPE : Desain Sistem PLTS On-Grid pada Barbershop Gaul dengan menggunakan Helioscope - Vito Arnando (Institut Riset dan Publikasi Indonesia, 2023)
Indonesia is a tropical country where Indonesia has summer with an average radiation of 4.5 kwh/m2 per day. Based on this, Indonesia is classified as a country that has abundant potential for solar energy so that the most suitable and most efficient generator to use is a solar power plant. Barbershop Gaul is a building that is used as a pilot for the object of research in this project. This building has high electricity consumption so that the difference between income and expenses for electricity consumption is often a deficit. The amount of electricity consumption is contributed by several existing electronic equipment including shaving machines, air conditioners, water pumps and so on. To overcome this problem, this project aims to produce a PLTS system design using a simulation method using the helioscope application. In addition to producing a system design, this project further produces an overview of the monthly PLTS energy production, a summary of the system, power loss sources to its economic analysis including initial investment costs, payback period and potential profits that can be obtained. After carrying out this project, it was concluded that the On-Grid PLTS at Barbershop Gaul produces 1,243.8 kWh of electrical energy annually with an energy consumption of 2,662 kWh/year. Thus if a PLTS is installed, the electrical energy used from the PLTS is 1,243.8 kWh and the remaining 1,418.2 kWh is supplied by PLN so Barbershop Gaul needs to pay IDR 3,600,000 to PLN for electricity consumption. However, with the savings generated by implementing the ON-grid system, the business owner only pays Rp. 1,682,593/year. For the initial investment issued in the installation of PLTS, it is Rp. 19,094,480 with Return Of Investment 11.3 Years or 11 Years 3 months